Optimal Vaccination Policies for COVID-19 Considering Vaccine Doses Delays - Gianatti, J.; Lotito, P. A.; Neder, J. G.; Núñez, P. M.; Parente, L. A. (Trends in Computational and Applied Mathematics, 2023)
This work introduces a methodology to determine an optimal vaccination strategy for the COVID-19 disease with limited vaccination capacity, considering the delays between vaccine doses in order to minimize the number of deaths. The evolution of the pandemic in the city of Tandil, province of Buenos Aires, Argentina, is studied through a compartmental model, where the parameters involved are calibrated according to official data. An auxiliary age-structured optimal control problem is introduced, where optimal policies are obtained taking into account the characteristics of the vaccine and the vaccination capacity. Through numerical simulations, the policy obtained is compared with other feasible strategies, considering or not strict isolation measures.